Teachers’ Instructional Workload Management and Students’ Academic Performance in Public and Private Secondary Schools in Akoko North-East Local Government, Ondo State, Nigeria (American International Journal of Education and Linguistics Research, 2018)
The study examined teachers’ workload and determined its implication on students’ academic performance in secondary schools in Akoko North East Local Government Area of Ondo State. Descriptive design of the survey type was adopted and a stratified random sampling was used to select 12 schools, which were 6 public and 6 private secondary schools, involving 132 participants who included 120 teachers and 12 principals. A self-constructed questionnaire titled “Teachers’ Workload and Student’s Academic Performance Questionnaire” (TWSAPQ), was administered. Five (5) hypotheses were tested using Pearson’s product moment correlation (PPMCC) and T-test at p